Promoting Environmental Knowledge Towards Community Independence in Waste Management: Developing A Gamification Module Based on Nggusu Waru Local Wisdom - Abbassyakhrin, Abbassyakhrin; Rahmawati, Anita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Environmental knowledge is a fundamental foundation for shaping community independence in waste management. This study aims to develop a gamification-based module integrating the eight pillars of Nggusu Waru local wisdom to enhance students' environmental knowledge as a basis for achieving community self-reliance in waste management. This Research and Development (R&D) employed the Dick and Carey model, involving seventh-semester students at Universitas Nggusu Waru Bima. Data were collected through expert validation sheets, student response questionnaires, environmental knowledge tests (pretest-posttest), observation, and interviews. The results showed that the module was highly valid (material expert: 4.63, media expert: 4.53) and practical (4.58). The module's effectiveness was demonstrated by a significant increase in environmental knowledge scores with an N-Gain of 0.63 (medium category) and high student engagement (87%). The integration of Nggusu Waru values successfully connected environmental knowledge with local cultural wisdom, creating a strong foundation for developing community independence in waste management. This study concludes that the gamification module based on Nggusu Waru local wisdom is valid, practical, and effective in enhancing environmental knowledge as a step toward community self-reliance in waste management